Chromosomal differentiation of Hyla nana and Hyla sanborni (Anura, Hylidae) with a description of NOR polymorphism in H-nana - Medeiros, L. R.; Rossa-Feres, D. C.; Recco-Pimentel, S. M. (Oxford University Press, 2003)
Specimens of Hyla nana and Hyla sanborni from a syntopic population were studied cytogenetically. These species are morphologically very similar and are frequently misidentified, confused with each other. Both species had a diploid chromosome number, 2n = 30. However, the karyotypes of H. nana and H. sanborni differed considerably from each other in the number of submetacentric and telocentric chromosomes. The two species also differed in their primary NOR-bearing chromosomes (metacentric pair 13 in H. nana and telocentric pair 12 in H. sanborni). Additional nucleolus organizer regions (NORs) were detected by Ag-NOR staining and FISH in chromosome pairs 1, 5, 6, 12, and 14 in seven specimens of H. nana. Thus, a total of six patterns of NOR were identified. These differences in karyotype and in NOR location allowed the unambiguous identification of syntopic individuals of the two species. However, the chromosomal morphology of both species differed from that reported for populations from other geographic regions, suggesting that a systematic reevaluation of this group of Hyla may be necessary.